1995
DOI: 10.1074/jbc.270.44.26029
|View full text |Cite
|
Sign up to set email alerts
|

A Single Point Mutation Switches the Specificity of Group III Src Homology (SH) 2 Domains to That of Group I SH2 Domains

Abstract: Stimulation of cellular responses by growth factors and cytokines is often accomplished by the activation of protein-tyrosine kinases (1, 6). One of the major consequences of tyrosine phosphorylation is to induce a specific set of protein-protein interactions, and thereby initiate a series of intracellular signaling cascades. The SH2 1 domains of cytosolic signaling proteins mediate the assembly of such complexes by binding to phosphotyrosine moieties within specific sequence contexts (1, 6, 7). Therefore, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 13 publications
1
59
0
Order By: Relevance
“…This result also demonstrates how easily SH2 domains with new properties could be evolved. Two cases in which a single point mutation could switch the binding specificity have been reported (46,47), but two homologous SH2 domains possessing dramatically different binding preferences due to the difference in one residue has not been previously reported to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…This result also demonstrates how easily SH2 domains with new properties could be evolved. Two cases in which a single point mutation could switch the binding specificity have been reported (46,47), but two homologous SH2 domains possessing dramatically different binding preferences due to the difference in one residue has not been previously reported to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, peptide studies may not provide accurate estimates of SH2 binding speci®city since synthetic peptides may not mimic all the structural features of SH2 binding sites on autophosphorylated receptors. In fact, this may be particularly true for PLCg and src family members where it has been shown that binding is not determined solely by the three amino acids carboxy-terminal to the phosphorylated tyrosine (Alonso et al, 1995;Songyang et al, 1995;Pascal et al, 1994;Larose et al, 1995). The optimal sequence carboxy-terminal to phosphotyrosine that binds to the src SH2 domain has been determined from a library of phosphopeptides and was found to be pYEEI.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal sequence carboxy-terminal to phosphotyrosine that binds to the src SH2 domain has been determined from a library of phosphopeptides and was found to be pYEEI. The selectivity of the src SH2 domain was highest for a large aliphatic amino acid at position +3, with slightly lower selections at positions +1 and +2 (Songyang et al, 1995). The residues carboxy-terminal to tyrosine 821 (EiLpYVNMD) of the Ufo receptor, match this sequence at the +2 and +3 positions.…”
Section: Discussionmentioning
confidence: 99%
“…All known SH2 domains can be placed into four different groups on the basis of the amino acid at position ␤D5. The side chain at the ␤D5 position contacts pϩ1 and pϩ3 of the phospho-tyrosine ligand and has been shown to have a major effect on SH2 selectivity (3,24,25). In our set of control SH2 domains we included three closely related SH2 domains from signaling molecules Abl, Src, and Nck that are derived from the same group as Grb2 (group 1).…”
Section: Resultsmentioning
confidence: 99%